Verifiable secret sharing scheme without dealer based on vector space access structures over bilinear groups. Issue 2 (1st January 2018) - Wang, Na; Fu, Junsong; Zeng, Jiwen
Abstract : In general, most of the previous secret sharing schemes involve a secret dealer and a number of participants. The dealer generates a secret and then distributes the secret shares to the participants in a centralised manner, which may lead to the data tamper problem. A verifiable secret sharing scheme without dealer on vector space access structures over bilinear groups is presented. In particular, each participant can act as a 'dealer' and the secret in the proposed scheme is a random element generated by all the participants from a bilinear group. In addition, the performance of the proposed scheme in terms of security and computing complexity is analysed in detail and compared it with that of the scheme by Zhang and Zhang. The results show that the proposed scheme performs better in terms of computational cost.